2016
DOI: 10.1111/jppi.12150
|View full text |Cite
|
Sign up to set email alerts
|

Role of Anxiety as a Trait and State in Youth With Mild Intellectual Disability: Coping With Difficult Situations

Abstract: Although social integration of youths with intellectual disabilities improves their psychological adaptation, it nevertheless exposes them to a higher risk of stress. The author's goal was to verify the regulatory role of anxiety, respectively, as a trait and as a state in youth with mild intellectual disability who are coping with difficult situations. The study, involving a group of 120 students at the Education and Rearing Center in Kielce (Poland), used two psychological methods pertaining to a cognitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…The study suggests that young people with MID declare a wide range of strategies, both antisocial and prosocial, to cope with peers' humiliating or isolating acts. Therefore, the results are in agreement with much dynamic research on coping, emphasizing situational and intra-personal factors of behavior (Cohen-Gazith, 1996;Kurtek, 2016;Leffert et al, 2000). Nevertheless, the findings indicate that humiliation and isolation are mostly interpreted as negative by young people with MID.…”
Section: Discussionsupporting
confidence: 90%
“…The study suggests that young people with MID declare a wide range of strategies, both antisocial and prosocial, to cope with peers' humiliating or isolating acts. Therefore, the results are in agreement with much dynamic research on coping, emphasizing situational and intra-personal factors of behavior (Cohen-Gazith, 1996;Kurtek, 2016;Leffert et al, 2000). Nevertheless, the findings indicate that humiliation and isolation are mostly interpreted as negative by young people with MID.…”
Section: Discussionsupporting
confidence: 90%
“…Prevention of toxic stress further needs the deliberate application of strategies to reduce anxiety (Kurtek, 2016), to change avoiding or passive coping skills into more active ones (Masten and Barnes, 2018;van der Kolk, 2014), and to talk over experiences, such as Life Review and Life Story Work, (group)reminiscence, and (group)psychotherapy. These strategies have been proven useful for people with mild and moderate intellectual disability (Bai et al, 2014;Barber et al, 2000;Hamilton and Atkinson, 2009;Meininger, 2006;Van Puyenbroeck and Maes, 2009), and, as our focus group method shows, need not be difficult to execute.…”
Section: Elderly People With Intellectual Disability Reviewing Adversities and Stress-protection In Their Lives 20mentioning
confidence: 99%
“…Therefore, it is still unclear whether socially anxious adolescents with MID interpret ambiguous situations in a negative way comparable to adolescents with an average IQ. There are several studies that concluded that individuals with MID have similar coping strategies during difficult situations as individuals without MID (Da Costa, Larouche, Dritsa, & Brender, 2000;Fanurik, Koh, Schmitz, Harrison, & Conrad, 1999;Kurtek, 2016;Madland, Feinmann, & Newman, 2000). These findings might suggest that similar biases in information processing might also play a role in adolescents with and without MID.…”
Section: Introductionmentioning
confidence: 98%